Differences in the Implementation of Diversion in the Juvenile Criminal Justice System: Analysis of the Karawang Court Decision - Nuraeni, Rini; Gagarin Akbar, Muhammad Gary; Abas, Muhamad (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The use of diversion in Indonesia’s juvenile justice system aims to protect children from harmful stigmatization and provide rehabilitation. The objective of the study is to analyze the application of diversion in two court decisions: Decision Number 9/Pid.Sus-Anak/2022/PN Kwg and Decision Number 14/Pid.Sus-Anak/2022/PN Kwg. The research employs a normative juridical and descriptive-analytical approach through a literature review. The findings demonstrate that the application of diversion depends on the type of offense and the condition of the child. Decision Number 9 sentenced the child to 3 years and 6 months of imprisonment for a case of child sexual intercourse, whereas Decision Number 14 imposed 120 hours of community service for theft. The analysis reveals that judicial considerations are influenced by the severity and impact of the offense, and underscore the importance of balancing law enforcement with the protection of the child’s future. This research shows that judicial discretion plays a crucial role in determining the implementation of diversion, highlighting the importance of aligning legal enforcement with restorative justice and child protection principles.